2019
DOI: 10.3847/1538-4357/ab07b8
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Emissions of the Fe xxi 1354 Å Line from Flare Loops Experiencing Fundamental Fast Sausage Oscillations

Abstract: Inspired by recent IRIS observations, we forward model the response of the Fe XXI 1354Å line to fundamental, standing, linear fast sausage modes (FSMs) in flare loops. Starting with the fluid parameters for an FSM in a straight tube with equilibrium parameters largely compatible with the IRIS measurements, we synthesize the line profiles by incorporating the non-Equilibrium Ionization (NEI) effect in the computation of the contribution function. We find that both the intensity and Doppler shift oscillate at th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 49 publications
1
12
0
Order By: Relevance
“…Inspired by the work of Tian et al (2016b), Shi et al (2019) forward-modeled the response of the IRIS Fe XXI line to fast sausage modes in flare loops under NEI conditions. They found that the synthetic spectral signatures, in particular the phase difference between the intensity and Doppler-shift oscillations, are mostly consistent with the IRIS observations.…”
Section: Magnetic Reconnection In Flaresmentioning
confidence: 99%
“…Inspired by the work of Tian et al (2016b), Shi et al (2019) forward-modeled the response of the IRIS Fe XXI line to fast sausage modes in flare loops under NEI conditions. They found that the synthetic spectral signatures, in particular the phase difference between the intensity and Doppler-shift oscillations, are mostly consistent with the IRIS observations.…”
Section: Magnetic Reconnection In Flaresmentioning
confidence: 99%
“…This requirement is more stringent than that the wave period P = 2π/ω be much longer than the ionization and recombination timescales (1/ν C and 1/ν R ). Non-EI effects are therefore seen even in the study on the Fe XXI 1354 Å line emitted from flare loops, despite the high densities therein (Shi et al 2019a). That said, the non-EI computations differ from their EI counterparts only in intensity variations, whereas the Doppler shifts and Doppler widths hardly experience any influence.…”
Section: Thermal Emissionsmentioning
confidence: 90%
“…The issue with temporal cadence arises from the short period of FSMs, which led AVD13 to propose that the ionic fractions (fq) may not respond instantaneously to the temperature variations to maintain ionization equilibrium. Indeed, it was shown by Shi et al (2019a) that non-equilibrium ionization (non-EI) effects are negligible only when the angular frequencies ω of FSMs are far below the ionization and recombination frequencies (ν C and ν R ). This requirement is more stringent than that the wave period P = 2π/ω be much longer than the ionization and recombination timescales (1/ν C and 1/ν R ).…”
Section: Thermal Emissionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inspired by the fundamental FSMs measured in flare loops in T16, we forward-modelled the numerical results by using the FoMo code ) to obtain their observational signals. We perform the synthetic process by using the Fe XXI 1354 Å spectral line, which has been considered by Shi et al (2019) in their forward modeling effort associated with the above-mentioned IRIS measurements. In our case, however, the coronal loop with substructures therein is a more realistic consideration.…”
Section: Observable Propertiesmentioning
confidence: 99%